Potent Neutralization of Staphylococcal Enterotoxin B In Vivo by Antibodies that Block Binding to the T-Cell Receptor. Issue 21 (4th October 2019) - Chen, Gang; Karauzum, Hatice; Long, Hua; Carranza, Danielle; Holtsberg, Frederick W.; Howell, Katie A.; Abaandou, Laura; Zhang, Bojie; Jarvik, Nick; Ye, Wei; Liao, Grant C.; Gross, Michael L.; et al.
Abstract: To develop an antibody (Ab) therapeutic against staphylococcal enterotoxin B (SEB), a potential incapacitating bioterrorism agent and a major cause of food poisoning, we developed a "class T" anti-SEB neutralizing Ab (GC132) targeting an epitope on SEB distinct from that of previously developed "class M" Abs. A systematic engineering approach was applied to affinity-mature Ab GC132 to yield an optimized therapeutic candidate (GC132a) with sub-nanomolar binding affinity. Mapping of the binding interface by hydrogen–deuterium exchange coupled to mass spectrometry revealed that the class T epitope on SEB overlapped with the T-cell receptor binding site, whereas other evidence suggested that the class M epitope overlapped with the binding site for the major histocompatibility complex. In the IgG format, GC132a showed ∼ 50-fold more potent toxin-neutralizing efficacy than the best class M Ab in vitro, and fully protected mice from lethal challenge in a toxic shock post-exposure model. We also engineered bispecific Abs (bsAbs) that bound tetravalently by utilizing two class M binding sites and two class T binding sites. The bsAbs displayed enhanced toxin neutralization efficacy compared with the respective monospecific Ab subunits as well as a mixture of the two, indicating that enhanced efficacy was due to heterotypic tetravalent binding to two non-overlapping epitopes on SEB. Together, these results suggest that class T anti-SEB Ab GC132a is an excellent candidate for clinical development and for bsAb engineering. Graphical Abstract: Unlabelled Image Highlights: SEB is a potent incapacitating agent and a major cause of food poisoning. SEB neutralizing antibodies were identified from a synthetic antibody phage library. An antibody with picomolar binding affinity was generated by antibody engineering. The best antibody demonstrated superior in vitro and in vitro anti-toxin efficacy. An excellent lead for further development of anti-SEB therapeutics was reported.